General Notions of Pragmatics and the Spheres of Pragmatic Competence - Urinboyeva Guluzro Dushayevna (Zien Journals, 2023)
This article is devoted to the problems of Pragmatic competence which is a subfield of linguistics and semiotics that studies the ways in which context contributes to meaning. It also discusses pragmatic competence in Modern English.
Keywords: pragmatics; meaning; semantics; approach